Diazotrophic Cyanobacteria are Associated With a Low Nitrate Resupply to Surface Waters in Lake Tanganyika - Ehrenfels, Benedikt; Bartosiewicz, Maciej; Mbonde, Athanasio Stephano; Baumann, Kathrin B.L.; Dinkel, Christian; Junker, Julian; Kamulali, Tumaini M.; Kimirei, Ismael A.; Niederdorfer, Robert; Odermatt, Daniel; Pomati, Francesco; Sweke, Emmanuel A.; et al. (Frontiers in Environmental Science, 2021)
In Lake Tanganyika, blooms of nitrogen-fixing (diazotrophic) cyanobacteria emerge, when the upper water column re-stratifies after a period of upwelling and convective mixing. During this seasonal transition, diazotrophic cyanobacteria exploit the abundant phosphate and fix nitrogen after other phytoplankton taxa have consumed the available nitrate. However, it remains less clear, which mechanisms favour diazotrophic cyanobacteria under more heavily stratified conditions with lower levels of excess phosphate and persistent nitrate-depletion. Here, we collected profiles of physicochemical parameters, nutrients and photo-pigments, as well as the medium to large-sized phytoplankton community during two lake-wide cruises to elucidate to what extend the abundance of diazotrophic cyanobacteria in Lake Tanganyika may be controlled by the nitrate resupply through the thermocline into the euphotic zone. At stations where nitrate was depleted but phosphate remained available near the surface, high densities of diazotrophic cyanobacteria were associated with a low nitrate supply to surface waters. Our data provide first support for two conceptual scenarios, where the relative position of the thermocline and the euphotic depth may create a functional niche for diazotrophic cyanobacteria: when the upward transport of nitrate into the euphotic zone is reduced by a subjacent thermocline, diazotrophic cyanobacteria, comprising Dolichospermum and Anabaenopsis, are key players in the medium- to large-sized phytoplankton community. By contrast, a thermocline located within the euphotic zone allows for the rapid vertical transport of nitrate for a thriving nitrate assimilating phytoplankton community that evidently outcompetes diazotrophic cyanobacteria. This study highlights that, under nitrogen-depleted conditions, diazotrophic cyanobacteria can also grow in response to a reduced nutrient resupply to the productive surface waters.